The Spatial Landscape of the Bacterial Community and Bile Acids in the Digestive Tract of Patients With Bile Reflux - Yang, Ni; Xu, Jun; Wang, Xuemei; Chen, Ning; Su, Lin; Liu, Yulan (Frontiers in Microbiology, 2022)
Background: Bile reflux can lead to inflammation and increased intestinal metaplasia. Since bile acids can influence the gastrointestinal environment, it is possible that bile reflux may alter the gastric microbiota and potentially the oral or gut microbiota. Bile acids have a very complex interrelationship with microbiota. We aimed to explore the characteristics of the digestive tract microbiota and bile acids profile in bile reflux patients. Methods: This study included 20 chronic gastritis patients with bile reflux and 20 chronic gastritis patients without bile reflux. Saliva, gastric fluid and fecal samples were collected for bile acid testing. Buccal mucosal swabs, gastric mucosal tissues, and feces were collected for bacteria detection. The UPLC-MS/MS examined bile acids profiles. 16S rRNA gene sequencing was used to analyze the bacterial profile. Results: Bilirubin in the blood increased in bile reflux patients. No other clinical factors were identified to be significantly associated with bile reflux. 12-DHCA, 6,7-diketo LCA, and βHDCA decreased while TUDCA increased in saliva of bile reflux patients. Streptococcus, Capnocytophaga, Neisseria, and Actinobacillus decreased in oral mucosa of bile reflux patients while Helicobacter, Prevotella, and Veillonella increased. Gastric bile acid levels were generally higher in bile reflux patients. Gastric mucosal microbiota was highly stable. The changes in fecal bile acids were insignificant. Bifidobacterium, Prevotella_2, Ruminococcus, Weissella, Neisseria, and Akkermansia decreased in fecal samples from bile reflux patients; while Alloprevotella, Prevotella_9, Parabacteroides, and Megamonas increased. Conclusions: Our results demonstrate that bile reflux significantly alters the oral, gastric and intestinal bile acids profiles, but only influences the oral and gut microbiota composition. These findings indicate that bile reflux can modulate the gastrointestinal microbiota in a site-specific manner.